2009
DOI: 10.1073/pnas.0900843106
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression map of the Arabidopsis shoot apical meristem stem cell niche

Abstract: Despite the central importance of stem cells in plant growth and development, the molecular signatures associated with them have not been revealed. Shoot apical meristems (SAMs) harbor a small set of stem cells located at the tip of each plant and they are surrounded by several million differentiating cells. This imposes a major limitation in isolating pure populations of stem cells for genomic analyses. We have developed a system to isolate pure populations of distinct cell types of the SAMs, including stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
362
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(382 citation statements)
references
References 26 publications
17
362
1
2
Order By: Relevance
“…Our observation that root and shoot stem cells have specialized responses to DNA damage is in agreement with the enrichment for DNA repair genes seen in the transcription profile of shoot stem cells (38). Expression of DNA repair genes could be a sign that the stem cells are under stress, as suggested (38), or that these cells have a low threshold for activation of DNA repair, consistent with a general hypersensitivity to DNA damage.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our observation that root and shoot stem cells have specialized responses to DNA damage is in agreement with the enrichment for DNA repair genes seen in the transcription profile of shoot stem cells (38). Expression of DNA repair genes could be a sign that the stem cells are under stress, as suggested (38), or that these cells have a low threshold for activation of DNA repair, consistent with a general hypersensitivity to DNA damage.…”
Section: Discussionsupporting
confidence: 86%
“…Expression of DNA repair genes could be a sign that the stem cells are under stress, as suggested (38), or that these cells have a low threshold for activation of DNA repair, consistent with a general hypersensitivity to DNA damage. However, examination of the cell type-specific transcription profiles in the shoot and root meristems (38,39) did not provide obvious clues to the molecular basis for this hypersensitivity and did not reveal clear candidate genes that might mediate the cell death response downstream of ATM/ATR in the stem cells, except perhaps for the detection of AUTOPHAGY 8G (ATG8G) as one of the genes preferentially expressed in shoot stem cells (38).…”
Section: Discussionmentioning
confidence: 90%
“…3A), together with previously published data from cellsorted domains of the shoot apical meristem, i.e. domains expressing the CLAVATA3 or WUSCHEL (WUS) protein (Yadav et al, 2009). The whole inflorescence nodes from this study were only loosely connected to the shoot meristem nodes.…”
Section: Meristems But Not Whole Inflorescences Retain Basic Functionmentioning
confidence: 82%
“…Their work characterized a multitude of developmental transcriptional programs that are controlled in space and time. Profiling of gene expression from different cell samples of shoot apical meristems by Yadav et al (10) has further expanded the use of this approach. They isolated three celltype populations from shoot apical meristems and demonstrated that cell-type-expression profiling is sensitive in identifying transcripts expressed in specific subsets of shoot-meristem cells.…”
Section: Significancementioning
confidence: 99%